Surgical Complications and Long Term Follow Up of Live Related Kidney Donors, Encountered with Open Donor Nephrectomy: Single Center Study in Pakistan - Shakeel Haseeb Uddin Siddique, Muhammad Shoaib Mithani, Salman El Khalid, Abdul Wasay, Habib Ullah, Zeeshan Zafar, Shariq Anis Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: For renal transplant, a living donor nephrectomy is not without its hazards with a reported mortality rate of 0.02%. The laparoscopic donor nephrectomy (LDN) approach is becoming the standard of care in most centers worldwide. But open donor nephrectomy (ODN) is a viable alternative to the laparoscopic approach. We aimed to establish the fact that reflects the safety of ODN as an alternative when the laparoscopic approach is not available without compromising the expanding demands of donor nephrectomies for renal transplantation. Methods: From June 2017 through June 2019, we performed 56 open donor nephrectomies (ODN) at The Kidney Centre. Data collected on living donors included sex, body mass index (BMI), relationship to the recipient, pre-op and post-op creatinine level, pre-and post-op hemoglobin level, incision type, blood transfusion, any intraoperative complications according to the Clavien-Dindo classification (CDC) of Surgical Complications. Results: Brother was found to be the most frequent relation in our study. Left side ODN was done in 41 cases with an advantage of a longer length of the left renal vein. We did not encounter any significant complications in our study. Conclusion: Open donor nephrectomy is an important safe method to harvest kidneys for renal transplantation.